Some features of prevention of demineralization of hard tissues of teeth during orthodontic treatment of children with dental anomalies - A. A. Ismoilov; Sh. K. Razakova; Dzh. T. Makhmudov (Эндодонтия Today)
Aim. To study the effectiveness of remineralization and hygienic measures in the prevention of demineralization of hard tissues of teeth when using a fixed orthodontic structure in children and teenagers with dentoalveolar anomalies. Materials and methods. We examined 150 children and adolescents with anomalies of the dentition at the age of 12 to 16 years with fixed orthodontic structures. When starting orthodontic treatment of anomalies of the dentoalveolar system in children, we proceeded from the fact that the treatment and prophylactic methods of education consisted of two stages: 1st stage – general, where they explained in detail how to carry out an individual hygienic procedure in the oral cavity with controlled brushing of the teeth; Stage 2 – specialized, which includes the features of oral care in children with orthodontic appliances in these specific conditions, in accordance with the new dental clinical situation of the oral cavity. Results. The data obtained necessitate the conditions for successful prevention of orthodontic complications during corrective therapy of dentoalveolar anomalies are remineralizing therapy, the correct choice of methods and means of individual oral hygiene.